Evaluation of three different methods to prevent dialyzer clotting without causing systemic anticoagulation effect - Richtrova, Pavlina; Rulcova, Kamila; Mares, Jan; Reischig, Tomas (Artificial organs, 2011)
Thrombogenicity is one of the most important biocompatibility markers of artificial material. Anticoagulation is commonly used to reduce thrombogenicity of the extracorporeal circuit (ECC) during intermittent hemodialysis (IHD). In some situations, systemic anticoagulants are contraindicated. The aim of our study was to compare thrombogenicity parameters during IHD with three different methods without a systemic anticoagulation effect. In a prospective, randomized, and crossover study, we examined 10 stable patients during IHD with (i) regular saline flushes of ECC; (ii) regional citrate anticoagulation (RCA); and (iii) AN69 ST membrane after ECC priming according to the manufacturer's recommendations. Before IHD and after 10, 60, 120, and 240 min, we measured the platelet count and the plasma concentrations of platelet factor 4 (PF4) and thrombin/antithrombin complexes (TAT). All 10 procedures with RCA were successfully completed after 4 h, whereas 6/10 procedures with saline flushes and 5/10 procedures with AN69 ST were finished prematurely because of clotting (P < 0.05). The TAT production was significantly increased during saline flushes and AN69 ST compared with RCA (P < 0.05). Platelet activation demonstrated by rising PF4 was present during all three methods. Markers of coagulation cascade activation were progressively increasing during IHD with RCA, saline flushes, and AN69 ST. The activation was significantly lower during RCA, and according to thrombogenicity, RCA is the most effective among compared anticoagulation methods.
Keywords: klinické křížové studie; Humans; lidé středního věku; hemodialyzační roztoky; Platelet Activation; citráty; Renal Dialysis; Female; Aged; Platelet Factor 4; Hemodialysis Solutions; dialýza ledvin; senioři; lidé; heparin; hemokoagulace; Heparin; Citrates; ženské pohlaví; Male; Middle Aged; Blood Coagulation; aktivace trombocytů; trombocytový faktor 4; Cross-Over Studies; mužské pohlaví; prospektivní studie; antikoagulancia; Anticoagulants; Prospective Studies